Prevalence, Etiology, Antimicrobial Susceptibility Testing and Predictors of Urinary Tract Infection among Neonates with Clinical Sepsis - Unaiza Syed, Zahid Rashid, Zarmast Khan, Rabia Riaz, Ahmad Bilal, Qamar Uz Zaman, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: The most common pediatric infection is urinary tract infection (UTI). Neonates who suffer from neonatal sepsis remain among the most vulnerable to death and morbidity, especially in developing countries. The present study aimed to determine the prevalence, etiology, and susceptible antimicrobial agents of UTIs among neonates with clinical sepsis. Patients and Methods: This cross-sectional study was carried out on 128 sepsis diagnosed neonates admitted to the Department of Pediatrics, Microbiology and Infectious Diseases, Niazi Welfare Teaching Hospital, Sargodha from September 2021 to May 2022. All neonates aged ≤ 28 days diagnosed of clinical sepsis and consent provided by their parents/guardian were enrolled. An interviewed based questionnaire was used for data collection from neonate’s parents or caregiver. The questionnaire included information on the socio-demographics and clinical presentations of neonates, as well as maternal history and laboratory examinations. The history is taken from prenatal to postnatal, including birth weight analysis and birth conditions. Neonates underwent general and local examinations to determine their state of consciousness, vital signs, and weight. We examined the abdomen (for tenderness and abdominal distention) and the nervous system (to elicit suckling and motor reflexes). A hematological analyzer was used to test the full blood picture (FBP). SPSS version 27 was used for data analysis. Results: Of the total 128 neonates, there were 76 (59.4%) females and 52 (40.6%) male neonates. The overall mean age was 6.4 ± 0.36 days with majority of neonates 112 (87.5%) were < 7 days. The low birth weight and low Apgar score were found in 13 (10.2%) and 16 (12.5%) neonates respectively. Of all neonates, the failure to breastfeed was found in 26 (20.3%) being the most common clinical symptom followed by an increase in breathing rate 21 (16.4%), diarrhea 19 (14.8%), gritting 16 (12.5%), altered mental status 12 (9.4%), and jaundice 11 (8.6%). The incidence of UTI was 20.3% (n=26). The prevalence of separated bacterial agents such as Klebsiella pneumonia and Enterobacter spp. was 61.5% (n=16) and 38.5% (n=10) respectively. Ciprofoxacin and amikacin were both effective against 90% and 60% of the bacterial isolates, respectively. The UTI potential predictors involved prolong labour, positive leucocyte esterase test, Low Apgar score, and positive urine nitrite test. Conclusion: The present study found that the prevalence of UTI was 20.3%. Failure to breastfeed was the most common clinical symptom followed by an increase in breathing rate, diarrhea, gritting, altered mental status, jaundice, convulsion, and cyanosis. Klebsiella pneumonia and Enterobacter spp. were the most prevalent separated bacterial agents. Ciprofoxacin and amikacin were both effective in bacterial isolates. Keywords: UTI, Clinical sepsis, Neonates, Antibiotic sensitivity